2016
DOI: 10.1177/0363546516659656
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Revision Hip Arthroscopic Surgery in Adolescent Patients Compared With a Matched Cohort Undergoing Primary Arthroscopic Surgery

Abstract: In conclusion, young patients who required revision hip arthroscopic surgery showed significant improvement in patient-reported outcome scores; however, final outcome scores in the revision group for sport activity, general health, and satisfaction were lower than those in the primary group. Patients who underwent 1 revision surgical procedure had higher outcome scores than patients who underwent more than 1 revision surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…Recent studies have reported that patients undergoing revision hip arthroscopy have lower baseline scores and outcomes at 2 years. 5 , 18 Domb et al 5 evaluated 107 cases of revision hip arthroscopy and compared these with a large cohort of patients who underwent primary hip arthroscopy. They determined that patients undergoing revision hip arthroscopy had worse measures of joint pain and function at all time points measured.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that patients undergoing revision hip arthroscopy have lower baseline scores and outcomes at 2 years. 5 , 18 Domb et al 5 evaluated 107 cases of revision hip arthroscopy and compared these with a large cohort of patients who underwent primary hip arthroscopy. They determined that patients undergoing revision hip arthroscopy had worse measures of joint pain and function at all time points measured.…”
Section: Discussionmentioning
confidence: 99%
“…A number of labral tears found in our study may have been present even before surgery; therefore, we decided to call these "residual" labral tears. However, it is known from studies of patients undergoing revision hip arthroscopy that labral repairs and additional labral débridement is often performed during revision surgery (25), so some of the labral tears found are actually clinically relevant labral tears. However, our study design did not allow us to further investigate the relevance of these labral tears.…”
Section: Discussionmentioning
confidence: 99%
“…These adhesions have been suspected as an important cause of softtissue impingement, restricted range of motion, and pain after hip arthroscopy (9,26). In a recent cohort study (25), painful adhesions were seen at revision surgery in nine of 42 patients (21%) who underwent arthroscopic hip surgery. As a consequence, capsular adhesions are a common reason for revision surgery (9,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 9 of 42 patients (21%) in a recent revision hip arthroscopy study were suspected to have painful adhesions preoperatively. 35 Symptomatic intra-articular adhesions can be successfully released by arthroscopic adhesiolysis. 31,32,34,36 In contrast, a recent magnetic resonance arthrography (MRA) study comparing the frequency and size of postoperative intra-articular adhesions in three locations in asymptomatic and symptomatic postoperative FAI patients detected no significant differences of capsular adhesions between the study groups.…”
Section: Adhesionsmentioning
confidence: 99%
“…12,32 Overall, it can be concluded that intra-articular adhesions are common, they occur with the same frequency in asymptomatic and symptomatic patients after FAI surgery, and they are not necessarily linked with symptoms in the postoperative FAI patient. 12,35 At our institution, an injection technique addressing the femoral head instead of the femoral neck for MRA is the most favored injection approach in postoperative patients to avoid contrast injection into the intra-articular adhesions. Hence the femoral head contrast injection technique should reduce the likelihood of an extra-articular contrast material leakage related to the injection path compared with a femoral neck injection technique.…”
Section: Adhesionsmentioning
confidence: 99%